Experimental procedure for EM characterization of tattoo inks in the framework of potential MRI interactions. (1st July 2020) - Zanovello, U.; Borsero, M.; Ferrara, E.; Giordano, D.
Highlights: Study of tattoos safety issues in modern MRI exams: electromagnetic interactions. Ink solutions/pigments electric characterization with parallel plate electrodes. Ink solutions/pigments magnetic characterization with Vibrating Sample Magnetometer. Higher measured electrical conductivity values comparable to those of human tissues. Weak and colour dependent magnetic behaviour for both ink solutions and pigments. Abstract: An experimental method to characterize the electromagnetic properties of tattoo inks is proposed. The overall procedure is aimed to investigate possible safety implications related with Magnetic Resonance Imaging (MRI). In this work, the experimental analysis is demonstrated on five commercial different tattoo inks. Measurements have been carried out both considering the ink solutions and the powdered pigments obtained exsiccating the solutions. As expected, results show that the electric and magnetic properties related with various inks are considerably different, as well as they are between the ink and the obtained pigment. In this perspective, findings show the importance of a proper tattoo ink characterization as a preliminary step to perform further studies based, for example, on in-silico models.